Nurses' knowledge, perceived practice, and associated factors towards sterile techniques in major operation rooms at public hospitals in Addis Ababa, Ethiopia, 2022: a cross-sectional study - Yosef Wube Habtewold; Mehammed Adem Getnet; Kalkidan Bazezew Genetu; Ashenafi Worku Woretaw (BMC, 2024)
Abstract Introduction A sterile technique is a standard to reduce microorganism transmission during surgery. Gaps in knowledge and practice in sterile techniques by nurses are common causes of surgical site infections for surgical patients. Even though surgical site infection is a global problem due to lack of knowledge and practice, almost no study has been done in Ethiopia regarding nurses' knowledge and practice of sterile techniques in the operating room. Therefore, this study aimed to assess nurses' knowledge, practice, and associated factors of sterile techniques in Addis Ababa public hospitals, Ethiopia. Method An institutional-based cross-sectional study was conducted on 423 nurses who were working in sixty-six operation rooms at seven public hospitals in Addis Ababa, Ethiopia, from May 11 to June 26/2022. A simple random sampling method was employed to select study participants. A pre-tested, self-administered questionnaire was used to collect data. Data were entered by Epi-data version 4.6 and analyzed by SPSS version 25. Descriptive statistics were presented by text, table, and figure. Multivariable analysis was used to identify the association between the dependent variable and independent variables. Variables with a P-value < 0.05 were considered statistically significant. Result Nearly three-fifths (58.1%; 95%CI: 53.2 to 63.7) of respondents had good knowledge, and 56.1% with 95%CI (51.5 to 61.1) had good practice with respect to sterile techniques in the operation room. Training [AOR = 1.989; 95%CI (1.120 to 3.530)], availability of guidelines [AOR = 6.4; 95%CI (3.773 to 10.856)], and supervision [AOR = 2.963; 95%CI (1.693 to 5.184)] were associated with nurses' knowledge about sterile techniques in the operating room. Availability of guidelines [AOR = 1.890, 95%CI (1.123 to 3.182)], presence of supervision [AOR = 4.732; 95%CI (2.643 to 8.471)], and having good knowledge of sterile techniques [AOR = 5.419; 95%CI (3.087 to 9.512)] were associated with nurses' practice of sterile techniques in the operation room. Conclusion Operative theater nurses' knowledge and practice of sterile techniques were found inadequate. Training, supervision, availability of guidelines, and knowledge of nurses towards sterile techniques are factors associated with sterile techniques in the operating room. So, it is better to strengthen training, equip wards with standardized guidelines, and provide supervision, which is crucial to enhancing their knowledge and practice.